2018
DOI: 10.1074/jbc.m117.818377
|View full text |Cite
|
Sign up to set email alerts
|

A human xenobiotic nuclear receptor contributes to nonresponsiveness of Mycobacterium tuberculosis to the antituberculosis drug rifampicin

Abstract: Mycobacterium tuberculosis is the causative agent of tuberculosis (TB). It acquires phenotypic drug resistance inside macrophages, and this resistance mainly arises from host-induced stress. However, whether cellular drug efflux mechanisms in macrophages contribute to nonresponsiveness of M. tuberculosis to anti-TB drugs is unclear. Here, we report that xenobiotic nuclear receptors mediate TB drug nonresponsiveness by modulating drug efflux transporters in macrophages. This was evident from expression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…In a subsequent study, the same research group showed that PXR can modulate macrophage drug-efflux transporter expression and activity, compromising the effect of rifampicin in vitro in hMDMs (Fig 2) [92]. Previous studies showed that rifampicin is a potent PXR activator that can induce expression of important metabolizing enzymes [93].…”
Section: Pxrmentioning
confidence: 86%
See 1 more Smart Citation
“…In a subsequent study, the same research group showed that PXR can modulate macrophage drug-efflux transporter expression and activity, compromising the effect of rifampicin in vitro in hMDMs (Fig 2) [92]. Previous studies showed that rifampicin is a potent PXR activator that can induce expression of important metabolizing enzymes [93].…”
Section: Pxrmentioning
confidence: 86%
“…Previous studies showed that rifampicin is a potent PXR activator that can induce expression of important metabolizing enzymes [93]. In mice infected with M.tb, the PXR antagonist ketoconazole rescued the activity of rifampicin [92].…”
Section: Pxrmentioning
confidence: 92%
“…P‐gp, for instance, is highly expressed in lung tissues and alveolar macrophages, and its expression may be more relevant for pulmonary concentrations rather than plasma levels. In human tissues and in a mouse model, PXR activation has been shown to reduce the effect of RIF . Several pathways leading to inflammatory processes have been shown to be controlled by PXR, thus potentially being variable among individuals in terms of appropriate immune response and microbe killing .…”
Section: Discussionmentioning
confidence: 99%
“…In human tissues and in a mouse model, PXR activation has been shown to reduce the effect of RIF. 35 Several pathways leading to inflammatory processes have been shown to be controlled by PXR, thus potentially being variable among individuals in terms of appropriate immune response and microbe killing. 36 The high heterogeneity in causes of death did not allow for exploring the association for specific unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One key mechanism appears to involve direct interactions between RIF and nuclear receptors. For example, it has been shown that RIF activates pregnane X receptor (PXR) that can promote TB growth in macrophages via increased efflux of TB-drugs out of the cell (123). This leads to sustained bacterial growth in the presence of the drug, which may accelerate the development of resistance.…”
Section: Antibiotics and Effects On Host Immunitymentioning
confidence: 99%